The CADIS-DXTRAN method in NECP-MCX for Radiation Shielding Simulations - Huang Zhanpeng; Cao Liangzhi; He Qingming; Wu Hongchun (EPJ Web of Conferences)
This paper discusses the implementation of the Consistent Adjoint-Driven Importance Sampling-Deterministic Transport (CADISDXTRAN) method in NECP-MCX to speed up Monte Carlo simulations for neutron radiation shielding applications. It provides a brief theoretical overview of the CADIS-DXTRAN method and describes the coding process in NECP-MCX. The study compares the performance of the CADIS-DXTRAN method with the CADIS method and the DXTRAN method in a labyrinth problem and a channel shielding problem. The results of the labyrinth problem reveal that the CADIS-DXTRAN method is highly efficient with a Figure of Merit (FOM) value 45 times that of DXTRAN and 17 times that of the CADIS method. While there is no significant improvement of the CADIS-DXTRAN method in the channel shielding problem. The particle behavior in the two problems is analyzed in detail to explain the performance of the CADIS-DXTRAN method.